Effects of forest fragmentation on the winter body condition and population parameters of an habitat generalist, the wood mouse Apodemus sylvaticus: a test of - Díaz, M.; Santos, T.; Tellería, J. L. (Acta Oecologica, 1999)
Three main causal hypotheses have been proposed to explain the inverse relationships between habitat patch size and density of gen- eralist mouse species in fragmented habitats: 1) enhanced habitat conditions as habitat patch size decreases; 2) inhibited emigration of excess indi- viduals in small and isolated habitat patches; and 3). reduced territoriality in small patches because they are occupied temporarily by non- reproductive individuals. From the mechanism underlying each hypothesis, we derived predictions on the effects of fragment size on the body condition of individuals (measured both as absolute body size and as body mass relative to body size) and some demographic parameters of mouse populations redated to reproductive output (sex-ratio and proportions of sexually active and recently-born individuals), and we tested such predic- tions with data from wood mice Apodemus sylvaticus wintering in three Spanish forest archipelagos in which the inverse relationship between for- est patch size and mouse abundance had been previously proven. No differences in average body size or in average body mass relative to body size were detected among fragments. Mouse populations wintering in small fragments showed more male-biased sex-ratios, a larger proportion of sex- ually active adults and fewer juveniles as compared to mouse populations wintering in large fragments nearby. Results clearly rejected the third hypothesis and did not support the second one. It thus seemed that habitat conditions for mice improved as forest fragment size decreased, although the expected positive effects on individuals could have been prevented by relaxed territoriality and increased food resource depletion by denser mouse populations. Bearing in mind the negative effects of dense wood mice populations on the distribution, abundance and population dynamics of forest species, this apparent enhancement of habitat conditions for mice in small forest fragments could have far-reaching conse- quences for the long-term persistence of such fragments.
Keywords: Body condition; Body size; demography; Forest fragmentation; population density; winter; wood mouse

Vertebrate predation on Holm Oak, Quercus ilex, acorns in a fragmented habitat: effects on seedling recruitment - Santos, T.; Tellería, J. L. (Forest Ecology and Management, 1997)
Rodent and avian consumption of Holm Oak, Quercus ilex, acorns were examined in central Spain during two high-production seasons, 1990-1991 and 1993-1994, in 1 and 3 large stands and in 6 and 10 small stands (0.2-12 ha) respectively, to study the effects of vertebrate predation on seedling recruitment. Previous data indicate that wood mouse abundance is much higher in small stands. Tree size, frequency of acorn-bearing oaks and acorn abundance were similar in the two sizes of forest stands. Overall acorn consumption was 33.7 times higher in the small stands compared to that in the large stands in 1991, and 3.1 times larger in 1994. Consumption of acorns by mice in the small stands was 49 and 95 times greater than that by birds in the first and second year, respectively. Seedling recruitment was significantly higher in the large stands in both study seasons. Regeneration by ramets was roughly similar in small and large stands in both seasons. Thus, predation by mice was apparently responsible for the failure of sexual reproduction in the small stands. The results suggest that vegetative regeneration might be the prevalent reproductive method of Holm Oaks in small forest tracts.
Keywords: acorns; Forest fragmentation; oak; Seedling; Vertebrate predation